Exploratory imaging outcomes of a phase 1b/2a clinical trial of allopregnanolone as a regenerative therapeutic for Alzheimer's disease: Structural effects and functional connectivity outcomes. Issue 1 (14th March 2022) - Raikes, Adam C.; Hernandez, Gerson D.; Matthews, Dawn C.; Lukic, Ana S.; Law, Meng; Shi, Yonggang; Schneider, Lon S.; Brinton, Roberta D.
Abstract: Introduction: Allopregnanolone (ALLO), an endogenous neurosteroid, promoted neurogenesis and oligogenesis and restored cognitive function in animal models of Alzheimer's disease (AD). Based on these discovery research findings, we conducted a randomized‐controlled phase 1b/2a multiple ascending dose trial of ALLO in persons with early AD (NCT02221622) to assess safety, tolerability, and pharmacokinetics. Exploratory imaging outcomes to determine whether ALLO impacted hippocampal structure, white matter integrity, and functional connectivity are reported. Methods: Twenty‐four individuals participated in the trial ( n  = 6 placebo; n  = 18 ALLO) and underwent brain magnetic resonance imaging (MRI) before and after 12 weeks of treatment. Hippocampal atrophy rate was determined from volumetric MRI, computed as rate of change, and qualitatively assessed between ALLO and placebo sex, apolipoprotein E ( APOE ) ε4 allele, and ALLO dose subgroups. White matter microstructural integrity was compared between placebo and ALLO using fractional and quantitative anisotropy (QA). Changes in local, inter‐regional, and network‐level functional connectivity were also compared between groups using resting‐state functional MRI. Results: Rate of decline in hippocampal volume was slowed, and in some cases reversed, in the ALLO group compared to placebo. Gain of hippocampal volume was evident in APOE ε4 carriers (range: 0.6% to 7.8% increased hippocampal volume). Multiple measures of white matter integrity indicated evidence of preserved or improved integrity. ALLO significantly increased fractional anisotropy (FA) in 690 of 690 and QA in 1416 of 1888 fiber tracts, located primarily in the corpus callosum, bilateral thalamic radiations, and bilateral corticospinal tracts. Consistent with structural changes, ALLO strengthened local, inter‐regional, and network level functional connectivity in AD‐vulnerable regions, including the precuneus and posterior cingulate, and network connections between the default mode network and limbic system. Discussion: Indicators of regeneration from previous preclinical studies and these exploratory MRI‐based outcomes from this phase 1b/2a clinical cohort support advancement to a phase 2 proof‐of‐concept efficacy clinical trial of ALLO as a regenerative therapeutic for mild AD (REGEN‐BRAIN study; NCT04838301).